Genetic diversity into a novel free-living species of Bradyrhizobium from contaminated freshwater sediment - Zhang, Naxue; Jin, Chun-Zhi; Zhuo, Ye; Li, Taihua; Jin, Feng-Jie; Lee, Hyung-Gwan; Jin, Long (Frontiers in Microbiology, 2023)
A free-living Bradyrhizobium strain isolated from a contaminated sediment sample collected at a water depth of 4 m from the Hongze Lake in China was characterized. Phylogenetic investigation of the 16S rRNA gene, concatenated housekeeping gene sequences, and phylogenomic analysis placed this strain in a lineage distinct from all previously described Bradyrhizobium species. The sequence similarities of the concatenated housekeeping genes support its distinctiveness with the type strains of the named species. The complete genome of strain S12-14-2 consists of a single chromosome of size 7.3M. The strain lacks both a symbiosis island and important nodulation genes. Based on the data presented here, the strain represents a new species, for which the name Bradyrhizobium roseus sp. nov. is proposed for the type strain S12-14-2 T . Several functional differences between the isolate and other published genomes indicate that the genus Bradyrhizobium is extremely heterogeneous and has functions within the community, such as non-symbiotic nitrogen fixation. Functional denitrification and nitrogen fixation genes were identified on the genomes of strain S12-14-2 T . Genes encoding proteins for sulfur oxidation, sulfonate transport, phosphonate degradation, and phosphonate production were also identified. Lastly, the Bradyrhizobium roseus genome contained genes encoding ribulose 1,5-bisphosphate carboxylase/oxygenase, a trait that presumably enables autotrophic flexibility under varying environmental conditions. This study provides insights into the dynamics of a genome that could enhance our understanding of the metabolism and evolutionary characteristics of the genus Bradyrhizobium and a new genetic framework for future research.